Creating pathways for internationally educated teachers into the teaching profession: Practices, policies and problems in the Australian context. (March 2022) - Cruickshank, Ken
The diversity of teachers is half that of the student population in Australia. Despite government policies to support internationally trained teachers (ITTs), there remain major structural and institutional barriers working against access to the profession: an information gap, the lack of professional advice, the absence of programmes to help teachers gain accreditation and the lack of mentoring or support programmes. This paper focuses on ITTs undertaking volunteer teaching in community languages schools; these are community-run organisations where over 100, 000 children across Australia learn their home language. These sites were selected as they represent a key pathway into further study and employment for ITTs. Findings are drawn from online survey ( n =954) and interviews ( n =62) exploring professional strengths, needs and experiences. The key finding is the exclusion and 'problematisation' of ITTs, rather than recognition of the social, educational and economic benefits represented by this group. The article explores recent government-funded provision of pathways to teacher accreditation and the extent to which these address the barriers identified. There is a discussion of how such a model may be embedded in mainstream teacher education pathways.